Analysis of outcome and risk factors for failure after single-incision sling procedure (Annals of Medical Research, 2021)
Aim: To assess the effectiveness and safety of a single-incision sling (SIS) and to detect the risk factors for failure after surgery in woman with stress urinary incontinence (SUI).Materials and Methods: The medical records of the one hundred thirty-two patients were analyzed. Preoperatively, medical history was taken and urogynecological examination was made. Patients were asked to answer Urinary Distress Inventory (UDI-6) and Incontinence Impact Questionnaire (IIQ-7). Objective cure of SUI was defined as the absence of leakage of urine on the cough test. Subjective cure was based on negative response to UDI-6, question 3. Patients were divided into two groups according to objective cure rate: cured patients (Group A) and failed patients (Group B). Results: The overall objective and subjective cure was 87.8% and 90.1%, respectively. According to the objective cure rate, there were 116 patients (87.8%) in Group A and 16 patients (12.2%) in Group B. In terms of subjective cure, Quality of Life (QoL) scores (IIQ-7 and stress subdomain of UDI-6) of Group B were statistically improved after surgery (p=0.001 and p=0.005 respectively). When two groups were compared, Group B had higher prevalence of severe SUI (IIQ scores ≥15 points) and reduced urethral mobility (Q-tip ≤ 30°) (0.8% vs 87.5%, p=0.0001 and 3.4% vs 68.7%, p=0.0001, respectively). The overall recommendation rate for surgery was 90%.Conclusion: Our study showed that SIS procedure has high subjective and objective cure rates. The main risk factors for failure were detected as reduced urethral mobility and SUI severity expressed with IIQ scores.
Keywords: Suburetral slings; urinary incontinence; urinary stress incontinence